Pengembangan E-LKPD Berbasis Kontekstual dengan Media Liveworksheets pada Materi Lingkaran Di Kelas VIII - Muhammad Hammas Shalahuddin; Diesty Hayuhantika (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2022)
Learning media is one of the tools used by teachers to improve quality and overcome some learning problems. One of the problems that is often encountered by students is about understanding the concept. One of the learning media that can be designed to overcome this problem is student worksheets or LKPD. This study aims to describe the process and results of contextual-based E-LKPD development on class VIII circle material using live worksheets so that a valid and feasible product is produced. This research refers to a 4D development model that is modified into 3D (Define, Design, Develop). The results showed that the level of validity or feasibility of product development from the assessment of media experts got a percentage of 80.47% which was in the